1994
DOI: 10.1111/j.1600-0714.1994.tb00064.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA flow cytometry of reclassified subtypes of malignant salivary gland tumors

Abstract: Malignant salivary gland tumors are rare, constitute a heterogeneous group and are often difficult to diagnose histologically. This is borne out by the fact that in the present study 43.2% of 118 salivary gland tumors originally diagnosed as mucoepidermoid, acinic cell and adenoid cystic carcinomas had their original diagnosis altered upon reclassification. Patients with confirmed adenoid cystic carcinomas had a much worse prognosis than those with mucoepidermoid and acinic cell carcinomas. DNA flow cytometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
3
11
0
2
Order By: Relevance
“…Markers implicated in prognosis include DNA ploidy, 13 nucleolar-organizing regions, 14 Ki-67 antigen expression, 15 and S-phase value. 16 Previous DNA analysis of patients with ACC at our institution indicated a significant correlation between DNA ploidy and patient survival. 11 This analysis reviewed clinical aspects of the disease and tumor histological features only.…”
Section: Methodsmentioning
confidence: 98%
“…Markers implicated in prognosis include DNA ploidy, 13 nucleolar-organizing regions, 14 Ki-67 antigen expression, 15 and S-phase value. 16 Previous DNA analysis of patients with ACC at our institution indicated a significant correlation between DNA ploidy and patient survival. 11 This analysis reviewed clinical aspects of the disease and tumor histological features only.…”
Section: Methodsmentioning
confidence: 98%
“…Prognosis of patients with aneuploid malignancies is reported to be significantly worse than that of patients with diploid malignancies. [3][4][5]8 Recent studies showed that the percentage of cell proliferative rate such as SPF or (S + G2M) fractions is more useful than DNA ploidy for predicting prognosis and tumor activity. 3,4 However, there are negative studies also.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Cell proliferative fraction reflects in Sphase fraction (SPF) or S plus G2 plus M phases (S + G2M) fraction which serves as a marker for tumor activity. 1,3,4 These cytometric results have been primarily used in the prediction of tumor aggressiveness and prognosis, and therefore, to our knowledge, there is little literature focusing on its capability for diagnosing malignancies in the parotid gland. [1][2][3][4][5][6][7][8][9] From the radiologic aspect, many radiologists have attempted to find magnetic resonance imaging (MRI) features for predicting malignancy of the parotid gland with success to some extent.…”
mentioning
confidence: 99%
“…Offensichtlich aufgrund der geringen Häufigkeit von Speicheldrüsentumoren wurden die bislang durchgeführten DNA-Analysen vielfach an Paraffin-eingebettetem Material durchgeführt [1,2,5,7,14,16,28,33,40,45,46]. Die Sensitivität für den Nachweis aneuploider Zellpopulationen ist bei dieser Technik jedoch stark eingeschränkt, für eine Zellzyklusanalyse ist sie kaum geeignet [29].…”
Section: Patienten Und Methodenunclassified
“…Dieser Befund wird durch nahezu alle DNA-durchflusszytophotometrischen Untersuchungen bestätigt [2,5,12,14,16,17,40], auch wenn einige Untersuchungen von einem höheren Anteil maligner, aneuploider Speicheldrüsentumoren berichten [11,30,46] …”
Section: Patienten Und Methodenunclassified